(3TQM GdebOeI GdLRQjIs - (3eLghds ((3YeQ Hf jhSas)
(3ChdgG (B:s
(3HYO GdHSedI ; CMeO Gddg GdPj LYd GdbQGA ef NGUJg hCgdg hHYO aEf eHfi Yde GdJLhjO gh Yde jMUd dOjc Hg GdJegjO afXQJ HfXQ GdYHQI Ydi GdWdHI HVGYJge aj GdaUGMI bdjd hdPdc MGdge Hjf GdYhGde YSjQ NUhUG CHjGJ GdTjN GdcGed GdTjN eMeO Hf GdLRQj aQZHJ HGdJeGS EdMGM Le ZajQ Edi Cf CTQMgG ef CUOGagGs
(3BNQgG (B:s
(3GdMdb eMd GdcSQ hGdLQ GddSGf heMd GdaJM GdTag ajecf HgG hdG jecf HgeGs
(3aj Chdg hBNQg fbhds
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdMhGTj h GdJYdjbGJ (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs